Microscale heterogeneity of the soil nitrogen cycling microbial functional structure and potential metabolism - Shun Han; Xuesong Luo; Xiuli Hao; Yang Ouyang; Luyang Zeng; Li Wang; Shilin Wen; Boren Wang; Joy D. Van Nostrand; Wenli Chen; Jizhong Zhou; Qiaoyun Huang (Environmental Microbiology, 2021)
Summary Soil aggregates, with complex spatial and nutritional heterogeneity, are clearly important for regulating microbial community ecology and biogeochemistry in soils. However, how the taxonomic composition and functional attributes of N‐cycling‐microbes within different soil particle‐size fractions under a long‐term fertilization treatment remains largely unknown. Here, we examined the composition and metabolic potential for urease activity, nitrification, N 2 O production and reduction of the microbial communities attached to different sized soil particles (2000–250, 250–53 and 2 O production and reduction rates were greater in 2000–250 and 250–53 μm across different fertilizer regimes. The abundance of key N‐cycling genes involved in anammox, ammonification, assimilatory and dissimilatory N reduction, denitrification, nitrification and N 2 ‐fixation detected by GeoChip increased as soil aggregate size decreased; and the particular key genes abundance (e.g., ureC , amoA , narG , nirS / K ) and their corresponding activity were uncoupled. Aggregate fraction exerted significant impacts on N‐cycling microbial taxonomic composition, which was significantly shaped by soil nutrition. Taken together, these findings indicate the important roles of soil aggregates in differentiating N‐cycling metabolic potential and taxonomic composition, and provide empirical evidence that nitrogen metabolism potential and community are uncoupled due to aggregate heterogeneity.